"Love for China:" an ethnography of US-based Chinese international students' patriotism - Ping, Y (2022)
While the COVID-19 pandemic has wrecked havoc around the world, it has also caused upheavals to many Chinese international students studying in the US. Facing exorbitant prices of US-China airline tickets and stringent quarantine regulations, some of these previously mobile Chinese find themselves stranded in the US. Yet, they nevertheless declare their “love for China” after spending a majority of their adolescent and adult life abroad. Despite radical cultural and political differences between China and the US and the Chinese government’s unwelcoming gesture, they show an enduring bond to their motherland. Therefore, the following research questions are raised: In the contemporary context of China and the US, how do these international students negotiate patriotism—their “love for China”—while navigating educational and social terrains across the two nations? And more specifically, how is their institutional/lived experience in China and in the US able to reshape their understanding of and relation to these countries, and how do these well-educated youth reject, reconnect, and redefine Chinese patriotism over time as they mature academically in the US? This dissertation explores these questions by drawing on my ethnographic engagement with a dozen of young Chinese students, who have been pursuing their education in the US for at least a quarter of their lives. Through ethnographic interviews and observations, I show that the development of these Chinese international students’ patriotism is by no means a smooth transplant from China to the US but rather represents a fragmented, contingent process fraught with paradoxes and liminality. Defying simplification and dualism, these migrant students’ patriotism are under continuous negotiation. By dovetailing theoretical understanding with corporeal lived experience, contrasting privilege in China with challenges in the US, conjoining Chinese political resistance and US racial awakening, and combining Confucian epistemology with Enlightenment thinking, these US-based Chinese students approach their love for China in their unique, diasporic way. This ethnography of transnational patriotism attempts to capture the complex “love for China” of Chinese international students in the US.